(untitled) (Research, Society and Development, 2022)
Psychotropic drugs act on the central nervous system (CNS), producing changes in behavior, perception, thinking and emotions, and in some cases can lead to dependence. This study aimed to integrally evaluate the use of psychotropic drugs in primary care in the state of Piauí, and the state’s intervention plans. This bibliographic research follows a qualitative approach, not limited to numerical representation only, but also dedicated to a deeper article analysis. The basis used for data collection was the digital platform Rede UNA-SUS/Acervo de Recursos Educacionais em Saúde (ARES), using the keywords ’Psychopharmaceuticals, Primary Care and Indiscriminate Use of Medicines’. The articles selected date from 2017 to 2021; carried out in the state of Piauí and within the scope of Primary Health Care. We found 122 articles that, after sorting, resulted in: 90 articles (73.4%) within the temporal range, 40 (32.8%) within the scope of primary care and 10 (8.2%) in the state of Piauí; the sample used in this study was the latter. All of them presented intervention proposals through operational plans, identifying causes and applying corrective actions regarding the irrational use of drugs. The problem of the irrational use of these drugs is noticeable, and so is the importance of applying strategies and rectifying actions in order to raise awareness among the professionals and health establishments, as well as the population.